2009
DOI: 10.1177/0256090920090403
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Volatility and Cross Correlations in Stock Returns under Risk and Uncertainty

Abstract: Capital market efficiency is a matter of great interest for policy makers and investors in designing investment strategy. If efficient market hypothesis (EMH) holds true, it will prevent the investors to realize extra return by utilizing the inherent information of stocks. They will realize extra returns only by incorporating the extra risky stocks in their portfolios. While empirical tests of EMH and risk-return relationship are plentiful for developed stock markets, the focus on emerging stock markets like I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Similar types of results were reported by the regression model when we took transitory component and unexpected volatility component simultaneously in the regression equation in terms of both the contemporaneous as well as dynamic impact at 5 and 10 percent level. The unexpected variations in the market make the investors expect a risk premium for holding riskier emerging market assets (Kumar & Dhankar, 2009). The expectations of high risk premiums in the BRIC equity markets further reduce the stock market returns coupled with increased volatility adding to the fi nancial stress.…”
Section: Exhibit 10 Graphical Presentation Of the Conditional Variancesmentioning
confidence: 99%
“…Similar types of results were reported by the regression model when we took transitory component and unexpected volatility component simultaneously in the regression equation in terms of both the contemporaneous as well as dynamic impact at 5 and 10 percent level. The unexpected variations in the market make the investors expect a risk premium for holding riskier emerging market assets (Kumar & Dhankar, 2009). The expectations of high risk premiums in the BRIC equity markets further reduce the stock market returns coupled with increased volatility adding to the fi nancial stress.…”
Section: Exhibit 10 Graphical Presentation Of the Conditional Variancesmentioning
confidence: 99%
“…This line of research provides the degree of sensitiveness of emerging stock markets towards global economic and non-economic shocks. The present study roots its investigation back to the French, Schwert and Stambaugh's (1987) and Kumar and Dhankar's (2009) studies, wherein attempts were made to examine the relationship between stock returns with expected and unexpected volatilities of a set of stock markets. They found a significant negative relationship between stock returns and unexpected changes in volatility, and a significant positive relationship between stock returns and expected volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a number of studies questioned this phenomenon and failed to report any dynamic relationship (Cheung & Lee, 1993;King et al, 1994;McClure et al, 1999). For example, Kumar and Dhankar (2009) investigate the cross correlation in expected and unexpected volatilities among South Asian stock markets. The study reports weak relationship between the expected and unexpected volatilities of the stock markets in question.…”
Section: Introductionmentioning
confidence: 99%
“…Correlations of stock market returns have been studied for decades (Atchinson et al, 1987;Bollerslev, 1990;Badrinath et al, 1995;Chan, 1993;Yu and Wu, 2001;Cohen et al, 1980;Conrad and Kaul, 1988;Ilina and Daragan, 2001a;Kumar and Dhankar, 2009; and many others) in the attempt to learn the market behavior for predicting trends and identifying hints for trading decisions. Stock market correlations have been attributed to information propagation including news and a variety of other factors that may impact the interrelations in the stock market on local or global scales.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that efficiency of diversification in foreign markets decreases due to global integration. On the other hand, Kumar and Dhankar (2009) analyzed correlations between South Asian stock markets (India, Sri Lanka, Pakistan, and Bangladesh) and reported weak interdependency between these markets and global stock markets. The question arises: what did cause these studies to result in contradicting conclusions?…”
Section: Introductionmentioning
confidence: 99%